Prenatal therapeutics and programming of cardiovascular function. (January 2019) - Brennan, Lesley J.; Goulopoulou, Styliani; Bourque, Stephane L.
Abstract: Cardiovascular diseases (CVD) are a leading cause of mortality worldwide. Despite recognizing the importance of risk factors in dictating CVD susceptibility and onset, patient treatment remains a challenging endeavor. Increasingly, the benefits of prevention and mitigation of risk factors earlier in life are being acknowledged. The developmental origins of health and disease posits that insults during specific periods of development can influence long-term health outcomes; this occurs because the developing organism is highly plastic, and hence vulnerable to environmental perturbations. By extension, targeted therapeutics instituted during critical periods of development may confer long-term protection, and thus reduce the risk of CVD in later life. This review provides a brief overview of models of developmental programming, and then discusses the impact of perinatal therapeutic interventions on long-term cardiovascular function in the offspring. The discussion focuses on bioactive food components, as well as pharmacological agents currently approved for use in pregnancy; in short, those agents most likely to be used in pregnancy and early childhood.